Enantioselective [2,3]-Wittig Rearrangement of Carboxylic Acid Derived Enolates by Tetradentate Chiral Lithium Amide - Yatsuzuka, Kenji; Kawasaki, Midori; Shirai, Ryuichi (Synlett, 2023)
A chiral lithium amide mediated enantioselective [2,3]-Wittig rearrangement of carboxylic acid enolate has been developed. The reaction proceeds through the formation of a chiral mixed aggregate that shields one enantioface of enolate anion to give a highly functionalized chiral α-hydroxycarboxylic acid.
Keywords: [2,3]-Wittig rearrangement; α-hydroxycarboxylic acids; chiral lithium amide; enantioselectivity; rearrangement